Fatty Acid and Hopanoid Adaption to Cold in the Methanotroph Methylovulum psychrotolerans - Bale, Nicole J.; Rijpstra, W. Irene C.; Sahonero-Canavesi, Diana X.; Oshkin, Igor Y.; Belova, Svetlana E.; Dedysh, Svetlana N.; Sinninghe Damsté, Jaap S. (Frontiers in Microbiology, 2019)
Three strains of aerobic psychrotolerant methanotrophic bacteria Methylovulum psychrotolerans, isolated from geographically remote low-temperature environments in Northern Russia, were grown at three different growth temperatures, 20, 10 and 4°C and were found to be capable of oxidizing methane at all temperatures. The three M. psychrotolerans strains adapted their membranes to decreasing growth temperature by increasing the percent of unsaturated fatty acid (FAs), both for the bulk and intact polar lipid (IPL)-bound FAs. Furthermore, the ratio of βOH-C16:0 to n-C16:0 increased as growth temperature decreased. The IPL head group composition did not change as an adaption to temperature. The most notable hopanoid temperature adaptation of M. psychrotolerans was an increase in unsaturated hopanols with decreasing temperature. As the growth temperature decreased from 20 to 4°C, the percent of unsaturated M. psychrotolerans bulk-FAs increased from 79 to 89 % while the total percent of unsaturated hopanoids increased from 27 to 49 %. While increased FA unsaturation in response to decreased temperature is a commonly observed response in order to maintain the liquid-crystalline character of bacterial membranes, hopanoid unsaturation upon cold exposition has not previously been described. In order to investigate the mechanisms of both FA and hopanoid cold-adaption in M. psychrotolerans we identified genes in the genome of M. psychrotolerans that potentially code for FA and hopanoid desaturases. The unsaturation of hopanoids represents a novel membrane adaption to maintain homeostasis upon cold adaptation.